The Weaponization of Water: Environmental Policy as a Tool of Russian Hybrid Warfare in the Caspian Sea - Chiragov, Fuad (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This article analyzes the Russian Federation's strategic weaponization of environmental policy in the Caspian Sea region as a sophisticated, non-kinetic instrument within its general hybrid warfare strategy. Avoiding the general assumption of environmental degradation as a byproduct of war, this analysis assumes that Russia is taking conscious measures in applying natural resources and environmental disasters as an heterogenous policy to accomplish political and economic objectives. By dominating the Caspian's principal water source, the Volga River, Moscow acquires the ability to inflict disproportionate, cumulative harm on the economies and legitimacy of governments of littoral states—specifically Kazakhstan, Azerbaijan, Turkmenistan, and Iran—without crossing the threshold of formal armed conflict. This piece outlines the mechanisms of this weaponization of the environment in physical and economic arguing that it is a central and expanding frontier of international competition, a key challenge to traditional understandings of national security.